PHILOSOPHICAL INTERPRETATION OF DREAMS IN THE THOUGHT OF AL-KINDI: ISLAMIC PERSPECTIVE AND PHILOSOPHICAL STUDY - Elmuna, Labib (Aqidah-Ta: Jurnal Ilmu Aqidah, 2024)
This article delves into the concept of dreams in Islamic thought, particularly through the philosophical approach developed by Al-Kindi, an early Muslim thinker. Dreams have long been a focus of study in various civilizations, including the rich philosophical and spiritual traditions of Islam. In works such as "Mahiyah an-Naum wa al-Ru'ya," Al-Kindi articulates an understanding of sleep, dreams, and their relation to the human soul from a profound philosophical perspective. This research employs qualitative methods and literary analysis to comprehend the phenomenon of dreams in the Islamic scholarly context. Primary data is derived from Al-Kindi's writings and other relevant scholarly works. The findings indicate that Al-Kindi interprets dreams as outcomes of the sleeping state where the soul utilizes its inner faculties, particularly through the concept of "khayal" or imagination. Al-Kindi's viewpoint offers new insights into the relationship between dreams, reason, and spiritual reality in Islamic thought.